Polymeric nanomedicine for cancer therapy - Park, Jae Hyung; Lee, Seulki; Kim, Jong-Ho; Park, Kyeongsoon; Kim, Kwangmeyung; Kwon, Ick Chan (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Nanomedicine, an offshoot of nanotechnology, refers to highly specific, molecular-scale medical intervention for treating disease or repairing damaged tissues. In recent years, polymer-based nanomedicine, a field that includes the use of polymer-DNA complexes (polyplexes), polymer-drug conjugates, and polymer micelles bearing hydrophobic drugs, has received increasing attention for its ability to improve the efficacy of cancer therapeutics. Owing to their small size and excellent biocompatibility, nanosized polymer therapeutic agents can circulate in the bloodstream for long periods of time, allowing them to reach the target site. In addition, chemical modification of polymer therapeutic agents with ligands capable of specifically binding receptors that are over-expressed in cancer cells can markedly augment therapeutic efficiency. This review highlights the characteristics of cancer that provide nanodrug targeting opportunities and discusses rational approaches for future development of polymeric nanomedicines. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: SELF-ASSEMBLED NANOPARTICLES; ACCELERATED BLOOD CLEARANCE; BLOCK-COPOLYMER MICELLES; MODIFIED GLYCOL CHITOSAN; GENE DELIVERY SYSTEM; LOW-MOLECULAR-WEIGHT; IN-VIVO; POLY(ETHYLENE GLYCOL); PLASMID DNA; TRANSFECTION EFFICIENCY